2013
DOI: 10.1159/000348359
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Mesenchymal Stem Cells in Chitosan/Collagen Microbeads for Orthopedic Tissue Repair

Abstract: Microencapsulation and delivery of stem cells in biomaterials is a promising approach to repairing damaged tissue in a minimally invasive manner. An appropriate biomaterial niche can protect the embedded cells from the challenging environment in the host tissue, while also directing stem cell differentiation toward the desired lineage. In this study, adult human mesenchymal stem cells (MSC) were embedded in hydrogel microbeads consisting of chitosan and type I collagen using an emulsification process. Glyoxal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 46 publications
1
73
0
1
Order By: Relevance
“…The approach presented here incorporates cells and a permissive matrix to create modular microtissues that mimic the native microenvironment and can be used as a scalable strategy to vascularize tissues. Fabrication of fibrin-based microtissues is rapid and facile, and populations of microtissues can be delivered minimally invasively via injection 63 .…”
Section: Discussionmentioning
confidence: 99%
“…The approach presented here incorporates cells and a permissive matrix to create modular microtissues that mimic the native microenvironment and can be used as a scalable strategy to vascularize tissues. Fabrication of fibrin-based microtissues is rapid and facile, and populations of microtissues can be delivered minimally invasively via injection 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has demonstrated that microbeads support osteogenic differentiation of bmMSC, 19 and that populations of microbeads can be collected and injected through a needle without the loss of cell viability. 18 Therefore, microbeads can be maintained in culture and exposed to desired differentiation conditions, and they can subsequently be collected and implanted without the need to disrupt the cellular microenvironment. Microbeads also can be combined with other types of biomaterials to create multiphase constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has previously employed modular tissue engineering techniques to fabricate three-dimensional (3D) cell-seeded hydrogel ''microbeads'' comprised of physiologically relevant proteins and polysaccharides, and has shown that they can be used as microenvironments to support osteogenic differentiation of embedded bmMSC. 18,19 We have also shown that composite matrices formed from collagen and fibrin (COL/ FIB) support the formation of vessel-like structures when seeded with a defined coculture of bmMSC and HUVEC. 20 In this work, we have combined osteogenically differentiated bmMSC-seeded COL/FIB/HA microbeads with a COL/ FIB matrix containing both bmMSC and HUVEC.…”
Section: Introductionmentioning
confidence: 94%
“…Importantly, the microbeads can then be collected without trypsinization of the cells, and can be injected as a paste in a minimally invasive manner. 38,39 Our group has previously shown that collagen and chitosan composite hydrogels fabricated by thermal gelation and initiation using b-glycerophosphate have strong potential as matrices for cell encapsulation and scaffolds for bone tissue engineering, 40 and that cross-linking with glyoxal can be used to reinforce the mechanical properties of the gel, while maintaining cytocompatibility. 41 Other investigators have also investigated the use of MSC encapsulated within collagen-based microspheres 42 for bone, 43 cartilage, 44,45 and osteochondral 46 tissue engineering.…”
Section: Introductionmentioning
confidence: 99%